The rise and fall of "Novorossiya": examining support for a separatist geopolitical imaginary in southeast Ukraine. Issue 2 (4th March 2017) - O'Loughlin, John; Toal, Gerard; Kolosov, Vladimir
Abstract: In the spring of 2014, some anti-Maidan protestors in southeast Ukraine, in alliance with activists from Russia, agitated for the creation of a large separatist entity on Ukrainian territory. These efforts sought to revive a historic region called Novorossiya ("New Russia") on the northern shores of the Black Sea that was created by Russian imperial colonizers. In public remarks, Vladimir Putin cited Novorossiya as a historic and contemporary home of a two-part interest group, ethnic Russian and Russian-speaking Ukrainians, supposedly under threat in Ukraine. Anti-Maidan agitation in Ukraine gave way to outright secession in April 2014, as armed rebel groups established the Donetsk People's Republic and Luhans'k People's Republic on parts of the eponymous Ukrainian oblasts. Rebel leaders aspired to create a renewed Novorossiya that incorporated all of eastern and southern Ukraine from Kharkiv to Odesa oblasts. To examine the level of support for this secessionist imaginary in the targeted oblasts, our large scientific poll in December 2014 revealed the Novorossiya project had minority support, between 20 and 25% of the population. About half of the sample believed that the concept of Novorossiya was a "historical myth" and that its resuscitation and promotion was the result of "Russian political technologies." Analysis of the responses by socio-demographic categories indicated that for ethnic Russians, residents of the oblasts of Kharkiv and Odesa, for older and poorer residents, and especially for those who retain a nostalgic positive opinion about the Soviet Union, the motivations and aims of the Novorossiya project had significant support.